Religious Individualisation - Fuchs, Martin; Linkenbach, Antje; Mulsow, Martin; Otto, Bernd-Christian; Bjørn Parson, Rahul; Rüpke, Jörg (Walter de Gruyter GmbH, 2020)
This volume brings together key findings of the research project 'Religious Individualisation in Historical Perspective' at the Max Weber Centre for Advanced Cultural and Social Studies. Combining a wide range of disciplinary approaches, methods and theories, the volume assembles over 50 contributions that explore and compare processes of religious individualisation in Asia, the Mediterranean, and Europe from antiquity to the recent past.